2021
DOI: 10.1109/access.2021.3063277
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Information Fusion-Based Matching Decision Method for Manufacturing Service Resource

Abstract: With the development of specialization, coordination and intelligence in the manufacturing service process, the issue of how to quickly extract potential resources or capabilities for distributed manufacturing service requirements, and how to carry out resource matching for manufacturing service requirements with correlated mapping characteristics, have become the critical issues to be addressed in the cloud manufacturing environment. Through the combination of the characteristics of relevance, synergy and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…In order to develop and measure career exploration behavior, Stumpf et al [28] developed a new measurement scale, which mainly involved three components they believe, such as exploring belief, exploring Process, and exploring reaction-among them; the exploration process was divided into personal self-exploration and environmental exploration [29,30]. According to the career exploration defined by Stumpf et al, it is found that the active behaviors of individuals at work are affected by career exploration.…”
Section: E Positive Relationship Between Career Exploration Andmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to develop and measure career exploration behavior, Stumpf et al [28] developed a new measurement scale, which mainly involved three components they believe, such as exploring belief, exploring Process, and exploring reaction-among them; the exploration process was divided into personal self-exploration and environmental exploration [29,30]. According to the career exploration defined by Stumpf et al, it is found that the active behaviors of individuals at work are affected by career exploration.…”
Section: E Positive Relationship Between Career Exploration Andmentioning
confidence: 99%
“…So it is noteworthy that future work self-salience has a remarkable influence on personal career development. Studies have found that future work self-salience has the capability to predict voluntary professional behavior [30]. Job seekers with more self-salient in future work will present higher career adaptability and a higher level of career adaptability [9].…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Crowdsourcing is an open-ended and collaborative process, and scholars have studied it in different aspects, including model representation [14,15], application scenarios [16][17][18], process control [19], and data analysis [20]. However, most studies focus on the macrolevel of crowdsourcing design.…”
Section: A Crowdsourcing Of Complex Objectsmentioning
confidence: 99%
“…With the rising demand for more diverse products, the job-shop production management has evolved from the traditional single-machine single objective problem or multi-machine single objective model to the production control of various products in small batches [1,2]. Since the production and processing environment contains many uncertain changes, the production manager must consider the production management of flexible job-shop from multiple angles, and solve this problem with closely correlated yet sometimes conflicting elements [3,4]. The production management of the multi-objective flexible job-shop is to make a compromise between the multiple constraints on the objectives [5][6][7].…”
Section: Introductionmentioning
confidence: 99%